Nursing Situation “The Art of Caring during the Process of Grief” - Mondragón Sánchez, Edna Johana; Ayala Zuluaga , Jose Enver (Revista Cuidarte, 2021)
This article analyzes a nursing situation derived from an experience by a nursing professional. It identified elements of nursing knowledge, like the vision of the nursing world. Based on the nursing situation, the following knowledge patterns were analyzed: personal, empirical, ethical, aesthetic, sociopolitical, and emancipatory. The Theory of Caring by Kristen Swanson, with its five processes, facilitated understanding the meaning of the family’s situation, promoting an attitude of hope, sharing the experience, guiding care actions. Analysis of the Nursing situation evidenced the importance of epistemology and ontology as support of professional care, as well as its utility in the professional praxis and nursing education.How to cite this article: Mondragón Sánchez Edna Johana, Ayala Zuluaga Jose Enver. Nursing Situation “the Art of Caring during the Process of Grief”. Revista Cuidarte. 2020;12(2):e1933. http://dx.doi.org/10.15649/cuidarte.1933
Keywords: Nursing Care; Nursing Theory; Narration; Knowledge; Critical Care; Art